PENGARUH LABA (RUGI) BERSIH DAN ARUS KAS BERSIH TERHADAP RETURN SAHAM PADA PERUSAHAAN MAN UFAKT UR AUTOMOTIVE AND ALLIED PRODUCTS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sitanggang, Abdonsius (Jurnal Manajemen dan Bisnis, 2011)
In manufacturing companies Automotive and Allied Products listed on the Indonesia Stock Exchange in 2006-2007 showed fluctuations of income (loss), net cash ï¬‚ows and stock returns and the consequences of the rise and fall of income (loss) and cash flows cause stock returns ï¬‚uctuate too . So the problem is formulated "the influence of income (loss) and net cash ï¬‚ow to stock return at manufacturing Automotive and Allied Products listed on the Indonesia Stock Exchange. " This study aimed to investigate the eï¬ect of income (loss) and net cash flow to stock return on the company manufacturing Automotive and Allied Products listed on the Indonesia Stock Exchange. Beneï¬ts of the research is as one of the considerations for potential investors in making investment decisions. The population in this study are all manufacturing Automotive and Allied Products listed on the Indonesia Stock Exchange observation period 20002007. The sample in this study is a population of around 19 companies with saturated sampling method. Hypothesis testing is performed using multiple linear regression models. The results of F-test (ANOVA test) showed that the net income (loss) (X1) and net cash flow (X2) jointly have a positive and significant impact on the company's stock returns Automotive and Allied Products listed on the Indonesia Stock Exchange, with significance level of 0.014